Synthesis, characterisation and anti-corrosion screening of co(ii) n-butylmethyl and co(ii) n-ethylbenzyl dithiocarbamate / Muhammad Faiz Abd Latif - Abd Latif, Muhammad Faiz (Faculty of Applied Sciences, 2017)
Nowdays, industrial sectors facing a major problem of corrosion on materials due to condition that cause by degradation on the surface of material by electrochemical reaction. The industrial sector are usually exposed to condition that can promote corrosion process, but the used of inhibitor is more likeable to prevent this problem. The new series of cobalt (II) dithiocarbamate complexes were successfully synthesised by using in situ method which are Co(II) Nbutylmethyldithiocarbamate and Co(II) N-ethylbenzyldithiocarbamate. The compounds were characterised by FT-IR, UV-Vis, gravimetric analysis, molar conductivity, and melting point measurement. Infrared spectra of the complexes showed that the thiouride band .υ(C N) appeared at 1480-1470 cm-1. The stretching band of υ(C S) was unsplitting and appeared between 1013-1010 cm-1 indicates the coordination mode of dithiocarbamate complexes is a bidentate. The melting points of the complexes were higher than the raw materials, as expected. The UV-Vis analysis showed two types of transitions, which are n→π* and π→π* in complexes. UV-Vis spectra are showed that the Co(II) complexes undergo d-d transition as can be seen from the presence of absorption peak at > 400 nm. The molar conductivity showed the both complexes were a non electrolyte. The gravimetric analysis showed the percentage of Co[BuMedtc]2 was 7.59 % and the percentage of Co[EtBenzdtc]2 was 4.33 %. The corrosion inhibition study showed that the inhibition efficiency increases in the sequence [Co[BuMedtc]2] >[Co[EtBenzdtc]2]. The inhibitor efficiency tends to increase as inhibitor concentration increase.